A phylogenetically controlled meta‐analysis of biologging device effects on birds: Deleterious effects and a call for more standardized reporting of study data. Issue 4 (4th December 2017) - Bodey, Thomas W.; Cleasby, Ian R.; Bell, Fraser; Parr, Nicole; Schultz, Anthony; Votier, Stephen C.; Bearhop, Stuart
Abstract: The use of biologging devices continues to increase with technological advances yielding remarkable ecological insights and generating new research questions. However, as devices develop and are deployed more widely, there is a need to update our knowledge of the potential ethical impacts to allow scientists to balance these against the knowledge gained. We employed a suite of phylogenetically controlled meta‐analyses on a dataset comprising more than 450 published effect sizes across 214 different studies to examine the effects of biologger tagging on five key traits in birds. Overall, we found small but significant negative effects of tagging on survival, reproduction, parental care. In addition, tagging was positively associated with foraging trip duration, but had no effect on body mass. Meta‐regressions revealed that flying style, migration distance and proportional tag mass were significant influences producing these deleterious effects, with attachment type and position additionally important covariates influencing survival‐ and reproduction‐based effect sizes. There was a positive correlation between the effects of tagging on survival and reproduction, highlighting that effects may be cumulative, with the full effects of tagging not necessarily apparent in studies focused on single traits. We discuss the tradeoff between these negative effects and the advances gained through the use of biologgers. Finally, given the number of studies from our initial literature search that lacked sufficient data for inclusion in analyses, we provide recommendations on the essential information that all biologging studies should report in order to facilitate future assessments of impacts on animals.